RANCANG BANGUN SISTEM INFORMASI BERBASIS DEKSTOP PADA KOPERASI MELATI - Kemal Farouq Mauladi (Universitas Islam Lamongan, 2018)
Applications, Plans to Build Desktop-Based Information Systems on Melati Cooperatives, as one form of organization are the implementing units of members of the welfare sector in this case especially small and medium entrepreneurs. In making the system, it is necessary to have a system design, the system design used is object-oriented design by making object diagrams, functional models, and ERDs and normalization techniques for data modeling